Science Teachers’ Learning Management Competency through Professional Learning Communities to Promote Scientific Creativity and Sustainable Development Goals (SDGs) - Supattra Unyaphatariyakool; Chowwalit Chookhampaeng; Jiraporn Chano; Chi Cheng Wu (ASEAN Journal of Educational Research and Technology, 2027)
This study examined guidelines and needs for developing science teachers’ learning management competency through a professional learning community approach to promote secondary students’ scientific creativity and support Sustainable Development Goals (SDGs). Data were collected from experts and science teachers using interviews and a questionnaire. Qualitative data were analyzed inductively, whereas quantitative data were summarized using means and standard deviations. The findings showed that the proposed training curriculum should integrate curriculum objectives, content, active learning, collaborative lesson development, authentic assessment, and reflection. Teachers reported a high development need, particularly for internet-based information searching, technology-supported instructional media, and varied teaching techniques. These findings guide sustainable teacher professional development and quality science education.